THE ROLE OF MENTAL STATE IN CONFLICT CORRESPONDENCE. EMOTOLOGY. (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
Theoretical views on the issue of Internet linguistics, social networks and the use of linguistic units in them, as well as the mental state of a person, were reflected in the previous chapters. In live interpersonal communication, certain information about the mental state of a person is revealed. In social networks, it is possible to identify and diagnose the characteristics of a person's mental state. Due to this, multimodal expressions in social networks provide an opportunity to obtain a lot of information about the author. In particular, emojis can also serve as a means of assessing the mental state.